Flexible Solution-Processable Black-Phosphorus-Based Optoelectronic Memristive Synapses for Neuromorphic Computing and Artificial Visual Perception Applications - Kumar, Dayanand (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 The Authors. Advanced Materials published by Wiley-VCH GmbH.